Cognitive Load as a Predictor of Depression among Undergraduates in Nigerian Universities - Osita Victor Ossai; Martha Ejor Etta (South Sulawesi Education Development (SSED), 2023)
In spite of increased mental health care resources at universities, depression rates continue to rise. This study examined cognitive load as a predictor of depression among undergraduate students at Nigerian universities. A correlational survey paradigm was utilized. A total of 1026 first-year students of the Faculty of Education and Pharmaceutical Sciences at the University of Nigeria were included in this study. In the study, 300 undergraduate students [100 males and 200 females] from Nigeria's University of Nigeria were surveyed. The study collected data using the Cognitive Load Questionnaire (CLQ) and Beck's Depression Inventory (BDI). CLQ had a reliability coefficient of 0.93, while BDI had a reliability coefficient of 0.90. Two research assistants administered the instruments to respondents. Simple regression was utilized for the research questions. A Fisher Z-test was used to test hypothesis two, while A linear regression t-test was used to test hypothesis one. In Nigerian universities, cognitive load does not significantly predict depression among undergraduates. Among Nigerian undergraduate students, 2.2% of their depressive symptoms are associated with cognitive load as a result of their gender. Other factors that influence depression among undergraduates in Nigerian universities, such as stress, need to be identified and appropriate measures taken to ameliorate the increasing trend of depression among undergraduates.